The Kashmir Issue and the USA Stand: The Influence of the USA on the Kashmir Issue (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The USA was immensely prone to Pakistan on the Kashmir issue. The American stand on the Kashmir issue from the very beginning was unsympathetic to India. The major Indian view regarding Kashmir was that Pakistan being an aggressor in Kashmir be asked to vacate the territory it illegally occupied. But Sir Zafrullah Khan of Pakistan, in a bid to divert the attention of the Security Council from the Pakistani aggression clearly sought to consider other matters like forcible and unlawful occupation of Junagarh, Manavadar and some other states in Kathiawar by India along with the Kashmir issue. Warren Austin, the US delegate supported the Pakistani stand in widening the scope of the dispute from that on Kashmir to include all other Indo-Pakistani problems.